An Empirical Study of Students' Satisfaction Towards on-Campus Foodservice Operations - Mas'Udah Asmui; Intan Nordiana Zainal Abidin; Nur Fallah Mohd Liezuardee; Nur Sabrina Mohd Suhaimy; Wafiqah Othman; Nurul Fazira Jamaludin (Journal of International Business, Economics and Entrepreneurship)
This study focuses to identify the factors that affect students’ satisfaction on-campus foodservice in university. The importance of service quality may affect overall service satisfaction about on-campus food service whereby university students and staff are the key customers where they usually dine-in after class hours, socialising with friends, and having options to purchase cheaper prices at university cafeteria. This study is conducted at Medan Selera Kompleks Tok Gajah, one of the significant food services in Universiti Teknologi MARA, Pahang Branch. Atmospheric, price fairness, food and beverages variety, and the quality of food and beverages show moderate level of satisfactions among students. The level of satisfaction of food service operations and management are similarly moderate. The service quality has affected students’ expectations and perceptions, making them disappointed and choose to order food from outside of campus. Providing nutritious and clean food, varying the menu based on the customer's preferences and demands, reasonable prices, and matching the quality of the food with comfortable and clean dining atmosphere are all significant factors in ensuring customers fulfilment.